Emlékezés Kovács Kálmánra, a magyar irodalomtörténet professzorára 1930–1983 - D. Magyari, Imre (Gerundium, 2017)
Remembering Kálmán Kovács, Professor for History of Hungarian Literature 1930–1983. In this piece of personal remembrance a onetime student recalls the figure, intellectual background and collegial ties of the literary scholar who was fated to meet an untimely death but who was highly esteemed both by his fellow colleagues and his students.